2021
DOI: 10.21323/2414-438x-2021-6-2-141-150
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbal supplements on development of internal organs and chemical composition of broilers muscles

Abstract: The present article presents data on effectiveness of adding a phytobiotic feed additive into the diet of broiler chickens, either additionally or replacing the feed antibiotic in the chicken fodder. It has been established that the introduction of a phytobiotic feed additive into the broilers’ diet, both additionally and by replacing the feed antibiotic, provided positive effect on poultry meat quality and gave no negative effect on development of internal organs. By the end of fattening the relative weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Fat content was not significantly different (p > 0.05), but cholesterol levels were significantly decreased (p < 0.05) and were relatively lower when compared with Ilavarasan et al [34], who showed that fat levels were 2.5-2.78%. Omede et al [13], Praptiwi et al [35], and Nowak et al [11] reported that V. amygdalina contained high flavonoid levels, which reduced bird meat fat [34,[36][37][38][39]. Furthermore, Tan et al [40] showed that flavonoids inhibited adipogenesis and increased lipolysis and apoptosis in adipose tissue cells, with reduced meat fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat content was not significantly different (p > 0.05), but cholesterol levels were significantly decreased (p < 0.05) and were relatively lower when compared with Ilavarasan et al [34], who showed that fat levels were 2.5-2.78%. Omede et al [13], Praptiwi et al [35], and Nowak et al [11] reported that V. amygdalina contained high flavonoid levels, which reduced bird meat fat [34,[36][37][38][39]. Furthermore, Tan et al [40] showed that flavonoids inhibited adipogenesis and increased lipolysis and apoptosis in adipose tissue cells, with reduced meat fat.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ], and Nowak et al . [ 11 ] reported that V. amygdalina contained high flavonoid levels, which reduced bird meat fat [ 34 , 36 39 ]. Furthermore, Tan et al .…”
Section: Discussionmentioning
confidence: 99%